ODELLING AND PROGNOSTICATION OF MACROECONOMIC DYNAMICS OF PROVIDING THE ECONOMIC SUSTAINABILITY TO THE ECONOMIC SECURITY THREATS - Marhasova, Viktoriya; Oleksandra, Sakun; Klymenko, Tetyana (Науковий вісник Полісся, 2017)
Urgency of the research. The necessary condition of upgrading the administrative decisions on the basis of more reliable analysis, prognosis and objective ground of strategic directions to provide steady development is an improvement of methodological bases and methods of estimation of level of sustainability of economy to the economic security threats. Target setting. Analysis of national economy development as a difficult socio-economic system on the current stage needs development of methodical approaches and tools, that will allow to estimate plenitude of realization of functions of socio-economic subsystems and get the integral picture of key problems and priority directions of the state development. Actual scientific researches and issues analysis. Among scientists, who were involved in the study of different aspects of modeling and prognostication of economic sustainability and threats to economic security are S. Zenchenko (2009), G. Ivashenko (2000), E. Kniazeva (1991), S. Achelis (1999) etc. Uninvestigated parts of general matters defining. There is a necessity of providing the new methods of economic prognostication as the way of estimation of the economic sustainability to the economic security threats. The model implementation and application of this process is need to be embedded. The research objective. The research task is to present the methodological approaches to the definition and estimation of the level of economic sustainability to the threats to economic security. The statement of basic materials. The article presents the methodological approaches to the definition and estimation of the level of economic sustainability to the threats to economic security. The sequence and structure of model of identification process of firmness to the economic security threats are elaborated on the basis of analysis of modelling methods and types of models. The applying of integral estimation of stability of economy to the economic security threats by the different indicators is offered and proved to be reasonable. Conclusions. Thus, the recreation of the marked sequence of structural-dynamic events in the context of development and realization of Strategy will have the expressed recurrence of forming, increase and use of strategic potential. Thus successive realization 14 stages of planning, reformatting and optimization of structural-dynamic descriptions of economy will be based on sound registration of essence and maintenance of management mechanism.